1999
DOI: 10.1002/(sici)1096-9853(199905)23:6<531::aid-nag980>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

DEM simulation of granular media—structure interface: effects of surface roughness and particle shape

Abstract: SUMMARYAn enhanced discrete element method for the numerical modelling of particulate media is presented. This method models a particle of general shape by combining several smaller particles of simpler shape, such as a circle, into clusters that act as a single larger particle. The clusters more accurately model the geometrydependent behaviour of the particles, such as particle interlock and resistance to rolling. The method is implemented within the framework of an existing DEM program without the introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(58 citation statements)
references
References 12 publications
1
57
0
Order By: Relevance
“…Many researchers have selected the modeling technique of binding several circular particles with a constant bonding strength to simulate the geometrical shape of particles through numerical analysis using DEM (Jensen et al, 2001;McDowell and Harireche, 2002;Cheng et al, 2003). Jensen et al (1999) conducted a DEM-based numerical analysis to study the in‰uence of particle shape on shear behavior by using clustered particles and non-clustered particles. More interlocking occurred with a rougher particle shape; as a result, high shear strength was proved.…”
Section: Literature Reviewmentioning
confidence: 62%
“…Many researchers have selected the modeling technique of binding several circular particles with a constant bonding strength to simulate the geometrical shape of particles through numerical analysis using DEM (Jensen et al, 2001;McDowell and Harireche, 2002;Cheng et al, 2003). Jensen et al (1999) conducted a DEM-based numerical analysis to study the in‰uence of particle shape on shear behavior by using clustered particles and non-clustered particles. More interlocking occurred with a rougher particle shape; as a result, high shear strength was proved.…”
Section: Literature Reviewmentioning
confidence: 62%
“…This takes place mainly in the direction against the applied load. Jensen et al [22] modeled soil by discrete element model and showed that in two dimensions, each particle brings three degrees of freedom to the model. In that study, each interparticle contact was modeled with a normaldirection spring and dashpot, and a spring-dashpot-slider assembly in the tangential direction.…”
Section: Stick Slip Mechanismmentioning
confidence: 99%
“…In that study, each interparticle contact was modeled with a normaldirection spring and dashpot, and a spring-dashpot-slider assembly in the tangential direction. From the investigation by Jensen et al [22], it seems to be possible that the stress chain in Leighton Buzzard Sand with sucrose may be stronger than that in the Leighton Buzzard Sand with de-aired water in all the aspects in two dimensions.…”
Section: Stick Slip Mechanismmentioning
confidence: 99%
“…This approach provides valuable information about the flow of dust, and the results are confirmed by experimental observations. Jensen et al (1999) presented an enhanced DEM for the numerical modelling of particulate media. This method models a particle of general shape by combining several smaller particles of simpler shape, such as a circle, into clusters that act as a single larger particle.…”
Section: Introductionmentioning
confidence: 76%